(untitled) (Damascus University Journal for engineering sciences, 2022)
Electroencephalographic (EEG) signal’s importance increases as the neurotechnology research and industry accelerate. Therefore, it is crucial to acquire noise-free signals by maximising the signal-to-noise ratio (SNR). Many methods are followed to clean the signals, such as band-pass filters and notch filters. More advanced preprocessing techniques, like independent component analysis (ICA), were also used. These methods can increase SNR, but it is also true that they increase computation time and have the risk of signal distortion. Hence, isolating the noise components in the acquisition stage is more reliable. This work provides a new method for noise reduction by developing an insulation cap (iCap). The designed iCap was inspired by the coaxial cable and had four isolation layers. The iCap was tested on 20 subjects by recording their EEG signals and comparing the cases when the iCap was worn and not worn. The findings revealed that this approach could successfully boost the SNR of the EEG signal in 53.87 % of the case by 57.45±5.93 %.